ABO and Rhesus Blood Group Frequency among Donors and Admitted Patients at Zawia Medical Center, AzZawya City, Libya - Rajaa Alshwesh; Zinab Elfituri; Entisar Omran; Enas Ramih (AlQalam Journal of Medical and Applied Sciences, 2024)
The identification and categorization of blood groups play a crucial role in transfusion medicine as it allows for safe and compatible transfusions. Among the various blood group systems, the ABO and Rhesus blood grouping systems have special clinical significance. Understanding the distribution and frequency of ABO and Rhesus blood groups within a specific community is essential for healthcare planning, especially when it comes to blood supply management and organ transplantation. Additionally, studies have also shown a relationship between ABO blood groups and the onset and spread of diseases. Therefore, this study was conducted to detect the distribution and frequency of ABO and Rhesus blood groups in AzZawya City, Libya. In this retrospective study, data from the blood bank at Zawia Medical Center were collected over three years to detect the distribution of ABO and Rh blood groups among 5187 donors and admitted patients. The result shows that blood group O is the dominant among all study subjects (45%), as well as, among males (48.2%), and females (42.2%). Blood group A is the second most common at 34.6% among total, 33% among males, and 36% among females. For Rhesus antigens 89.4% of study subjects were Rhesus positive, 87.3% for males and 80% for females. In addition, the results show a statistically significant association between gender and blood group distribution p<0.001. Knowing the most common blood types helps maintain adequate blood bank supplies. يلعب تحديد وتصنيف فصائل الدم دورًا حاسمًا في طب نقل الدم لأنه يسمح بنقل آمن ومتوافق. ومن بين أنظمة فصائل الدم المختلفة، تتمتع أنظمة فصائل الدم بأهمية سريرية خاصة. يعد فهم توزيع وتواتر فصائل الدم ABO و Rh ضمن مجتمع معين أمرًا ضروريًا للتخطيط الرعاية الصحية، خاصةً عندما يتعلق الأمر بإدارة إمدادات الدم وزرع الأعضاء. بالإضافة إلى ذلك، أظهرت الدراسات أيضًا علاقة بين فصائل الدم ABO وظهور وانتشار الأمراض. لذلك، أجريت هذه الدراسة لتحديد توزيع وتواتر فصائل الدم ABO و Rh في مدينة الزاوية، ليبيا. في هذه الدراسة الاستعادية، تم جمع البيانات من بنك الدم في مركز الزاوية الطبي على مدى ثلاث سنوات لتحديد توزيع فصائل الدم ABO و Rh بين 5187 من المتبرعين والمرضى المقيمين. أظهرت النتيجة أن فصيلة الدم O هي السائدة بين جميع المشاركين في الدراسة (45٪)، وكذلك بين الذكور (48.2٪) والإناث (42 .2٪). فصيلة الدم A هي ثاني أكثر الأنواع شيوعًا بنسبة 34.6٪ من إجمالي المشاركين، 33٪ من الذكور، و 36٪ من الإناث. بالنسبة لمستضدات Rh، كان 89.4٪ من المشاركين في الدراسة موجبًا لـ Rh، 87.3٪ للذكور و 80٪ للإناث. بالإضافة إلى ذلك، تُظهر النتائج ارتباطًا إحصائيًا مهمًا بين الجنس وتوزيع فصائل الدم p <0.001.. تساعد معرفة أكثر أنواع الدم شيوعًا في الحفاظ على إمدادات كافية لبنك الدم.